Radiosensitivity of Two Local Chili Varieties to Gamma Rays - Makhziah Makhziah; Djarwatiningsih Poengky Soedjarwo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Genetic variation is needed for developing new superior varieties in plant breeding.  Genetic variation of chili plants could be increased by inducing mutation with gamma rays irradiation. The aim of this study was to determine radiosensitivity of two local varieties of chili pepper by calculating the lethal dose values at LD20 and LD50. Chili pepper (Capsicum frutescens L.) seeds of local varieties origin from Tulungagung and Ponorogo were irradiated with cobalt-60 gamma rays at doses of: 0; 100; 200; 300; 400; 500; 600; 700; 800; 900; 1000 Gray (Gy); each as many as 50 seeds per dose of radiation. The irradiated chili seeds were grown in small polybags containing 1:1 mixture of soil and compost. Germination parameters of chili seeds was observed 30 days after planting (DAT) to determine lethal dose of 20 (LD20) and lethal dose of 50 (LD50). The results showed that increasing doses of gamma rays caused greater damage to chili seeds therefore the seeds were not able to germinate. Local Tulungagung Variety had LD20 and LD50 of 147.62 Gy and 409.52 Gy; and the Local Ponorogo variety had LD20 and LD50 of 90.3 Gray and 453.7 Gray. Local Tulungagung Variety was more sensitive to gamma rays than Local Ponorogo Variety. LD20 and LD50 can be used to get a lot of genetic variation and obtaining the positive mutants. Keywords:  Irradiation, Genetic variation, Lethal dose, Mutation